A Journey to Inclusion in Scopus: Lessons Learned from Millah: Journal of Religious Studies - Andriansyah, Yuli (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
This editorial details the procedure that the Editorial Team of Millah: Journal of Religious Studies followed to prepare for Scopus indexing. The quality of the journal has been improved by taking a number of actions, with the ultimate goal of bringing it into compliance with Scopus's defined minimal requirements. The Editorial Team has worked tirelessly to improve the Quality of Content, uphold the principles of the Peer Review Process, encourage a significant number of professionals to join the Editorial Board, and enforce Metadata Standards. Undoubtedly, these initiatives were meticulously carried out over a period of time, and they were not without obstacles. In addition, a large number of stakeholders, both internal and external to the faculty and the institution, were involved as partners in the implementation of these initiatives.